2014
DOI: 10.5194/bgd-11-13699-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative estimation and vertical partitioning of the soil carbon dioxide fluxes at the hillslope scale on a loess soil

Abstract: Both modelling and experimental approaches have been applied to assess C exchange fluxes at large spatial scales. Yet, these approaches are subjected to substantial limitations and uncertainties. Here, we aim to highlight two key mechanisms able to improve the estimation of the hillslope aggregated CO 2 fluxes: (i) the persistence of soil organic 5 carbon (OC) in deep colluvium deposits; and (ii) the physical controls on CO 2 fluxes along soil profiles. This study focuses on a sloping cropland in the central l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…We used gradient method to measure soil respiration rate, r g , following Wiaux et al (2014). The soils were packed into 280 plastic pots (with 0.27 m height, L, and 0.26 m diameter) with an initial field bulk density, and a closed chamber with volume of 5 9 10 -4 m 3 was connected with each pot.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used gradient method to measure soil respiration rate, r g , following Wiaux et al (2014). The soils were packed into 280 plastic pots (with 0.27 m height, L, and 0.26 m diameter) with an initial field bulk density, and a closed chamber with volume of 5 9 10 -4 m 3 was connected with each pot.…”
Section: Methodsmentioning
confidence: 99%
“…The CO 2 emission rate was measured with method suggested by Norman et al (1997) and Wiaux et al (2014) using Lambda device (Lambda, ADC Company, UK) every 3 days under greenhouse conditions (with *8-h darkness and *16-h lighting, relative humidity between 55 and 80%). Then Rr value was calculated by:…”
Section: Methodsmentioning
confidence: 99%
“…There have been many laboratory investigations of soil (soil samples) and field investigations of the soil surface in different ecosystems, and these have shown that a large portion of the organic carbon in soil is found in the surface horizon [1] [7]. However, to understand overall carbon cycling in an ecosystem it is necessary to understand the dynamics of carbon in the deeper soil horizons [6] [8].…”
Section: Introductionmentioning
confidence: 99%